The Proclivity to Rely on Professional Experience and Evidence-Based Policing: Findings From a Survey of High-Ranking Officers in the Israel Police - Jonathan-Zamir, Tal (Criminal justice and behavior, 2019)
Studies have identified that police officers often support and value evidence-based policing (EBP), but nevertheless prefer relying on experience when making decisions. Yet, policing scholars have paid little attention to the generality of this proclivity, the psychological mechanisms behind it, or to its implications for implementing EBP. The present study illuminates this phenomenon. We review its psychological foundations and use a survey of high-ranking officers from the Israel Police to examine its prevalence. We find that while officers support EBP overall, they believe that decisions should be based primarily on experience, not research. The two were found to be separate (although correlated) constructs. Furthermore, we find that the preference for experience as the basis for decision making is an overarching trait, not associated with personal-level characteristics. We discuss the implications of our findings and argue that attempts to implement EBP should recognize and work with this inherent psychological inclination.